Impact of Craniocerebral Hypothermia and Cryopreserved Cord Blood on Reproductive Function of Male Rats with Chronic Alcohol Intoxication - Lomakin , Іvan; Kudokotseva , Olga; Babiichuk , Vladyslav; Kryshtal , Yevhenii (Problems of Cryobiology and Cryomedicine, 2020)
Abstract: In this work, we have studied the impact of chronic alcohol intoxication (CAI) on reproductive function in male rats. Prolonged alcohol abuse has been shown to signiﬁcantly reduce the manifestation rate of sexual activation and testosterone level in blood serum of male rats with CAI following exposure to a receptive female, as well as to change their seminal ﬂuid composition. The rhythmic craniocerebral hypothermia (rCCH), combined with the administration of cryopreserved cord blood leukoconcentrate (cCBL) ensured to a greater extent the dynamics of functional integrity recovery of the CAI-altered reproductive system in male rats, if compared to each of these methods used solely. The authors have hypothesized the rCCH and cCBL to activate the hypothalamic-pituitary system, aﬀecting thereby the testosterone synthesis and spermatogenesis stimulation. Probl Cryobiol Cryomed 2020; 30(4): 369–379